Optimalisasi Literasi dan Numerasi: Mewujudkan Generasi Cerdas di SDN 173653 Desa Nelela - Yoseph Putra Laia; Noel Michael Putra Ziliwu; Notralnus Buulolo; Lexi Fernando Sihotang; Joe Agus M Waruwu; Atalisi Zalukhu (Lembaga Pengembangan Kinerja Dosen, 2025)
This service aims to identify factors that influence literacy and numeracy and evaluate the effectiveness of the literacy and numeracy improvement program in Nelela Village, SD N 173653. This study uses a quantitative descriptive approach with samples of students in grades 4, 5, and 6. Data were collected through literacy and numeracy tests, questionnaires, observations and interviews. The results of this service indicate that the average achievement of students in literacy and numeracy is still below the national standard, and the proportion of achieving the standard is still low. Factors such as limited resources, lack of teacher training and minimal parental support are cited as the main obstacles in improving literacy and numeracy skills. The literacy and numeracy improvement program implemented has succeeded in increasing the average student achievement, although there are still some obstacles that need to be overcome. The data shows that the average literacy and numeracy scores of students increased significantly after participating in this program. In addition, this service found that interactive learning methods and the use of educational technology have great potential to increase student interest and motivation. This service provides practical advice on improving literacy and numeracy in primary schools, including providing adequate learning resources, teacher training and development, using technology in learning and increasing parental involvement and support. By implementing these recommendations, it is hoped that the literacy and numeracy skills of students at SD N 173653 will improve significantly so that they are better prepared to face the next stage of education and academic challenges in everyday life.